Early pacemaker implantation for transcatheter aortic valve implantation is safe and effective. Issue 1 (26th December 2021) - Patel, Kush P; Lim, Wei Yao; Pavithran, Asha; Assadi, Rangeena; Wan, Daniel; Kennon, Simon; Ozkor, Mick; Earley, Mark; Sporton, Simon; Dhinoja, Mehul; Hayward, Carl; Muthumala, Amal; et al.
Abstract: Background: Permanent pacemaker (PPM) implantation is a common complication of transcatheter aortic valve implantation (TAVI). The optimum timing of PPM implantation is still unclear as conduction abnormalities evolve and a balance needs to be struck between conservative delays in the hope of conduction recovery and overutilization of pacing. This study aimed to assess the safety and efficacy of early PPM implantation, without an observation period, among TAVI patients. Methods: This is a retrospective, observational study of 1398 TAVI patients. Clinical and pacing data were collected at baseline, 30 days and at a median of 15 (4–21) months post‐TAVI. Study endpoints included PPM‐related complications, pacing utilization and hospital length of stay. Results: One hundred five patients (8.2%) required a PPM, of which 13 were implanted pre and 92 post‐TAVI. Seventy‐six percent required pacing for either second‐ or third‐degree heart block. Time to implantation for post‐TAVI PPM was 1 (0–3) day. Six patients experienced a pacing‐related complication‐ lead displacement ( n = 3), hematoma ( n = 2), and device infection ( n = 1). Pacing utilization defined as pacing >10% of the time or a pacing requirement at the time of the pacing check was demonstrated in 83% of patients. Multivariate analysis revealed complete heart block (CHB) was the only independent predictor of pacing utilization. Hospital length of stay for the post‐TAVI PPM group was longer than the group without PPM (4 [2–8] vs. 3 [2–4] days; p < .001). Conclusions: Early PPM implantation in TAVI patients is safe and majority of patients require pacing in the short and mid‐term.